Discussions of Authenticity, Style and Form in the Architecture from the Modern Period to the Present - Merve Artkan; Özlem Kandemir (Art-Sanat)
In the process of the modern period until today, social and technical developments have greatly changed all architectural productions. The reflections of the innovative and authentic ideologies of modernism, which reject the tradition, on architecture have turned into an international style in which only simplified abstract forms spread over time. As well as in the West, modern architecture began to be viewed as universal acceptance based on form in non-Western contexts. Also, in the 21st century, it is thought that a technological style that behaves like a modern international style has emerged because of the accelerated technical developments and changes in the society. This situation provokes a debate on style, authenticity and form which has been going on for nearly two hundred years. The purpose of the study is to bring that conceptual discussion from the past to the present. In this context, as a method in the study, a comparison is made between the modern and contemporary period architectures, which seem to be quite different, but in terms of results, there are similarities. The sample of the study is limited within the scope of residential buildings. With this sample, it offers a view of the concept of “authenticity”, which defines many components such as place, culture, material, technique, form, through the phenomenon of “style”.